Least Manipulable Envy-free Rules in Economies with Indivisibilities - Tommy Andersson; Lars Ehlers; Lars-Gunnar Svensson (Lund University, School of Economics and Management, Department of Economics, 2013)
We consider envy-free and budget-balanced allocation rules for problems where a number of indivisible objects and a fixed amount of money is allocated among a group of agents. In "small" economies, we identify under classical preferences each agent's maximal gain from manipulation. Using this result we find the envy-free and budget-balanced allocation rules which are least manipulable for each preference profile in terms of any agent's maximal gain. If preferences are quasi-linear, then we can find an envy-free and budget-balanced allocation rule such that for any problem, the maximal utility gain from manipulation is equalized among all agents.
Keywords: C71; C78; D63; D71; D78; 330; (Least) Manipulability; Envy-freeness; Budget-Balance; Indivisibilities.